2004
DOI: 10.1111/j.1365-2133.2004.06213.x
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied S-nitrosothiol-containing hydrogels as experimental and pharmacological nitric oxide donors in human skin

Abstract: Topical RSNOs produce a consistent, sustained and biologically effective release of NO on human skin in vivo, which offers advantages over currently available topical NO donors. Dermal nitrite concentration--the oxidation product of NO--is directly correlated with blood flow at low and moderate levels of blood flow. At high levels of blood flow, there is a reduction in dermal nitrite, which is presumed to be due to increased blood scavenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 27 publications
3
97
0
4
Order By: Relevance
“…The study suggested that F127 hydrogels might be used as the storage and controlled release material for S-nitrosothiols. A similar study was done by Seabra et al, [72] in which GSNO and SNAC were incorporated into Synperonic F-127 hydrogels [a triblock copolymer of poly(ethylene oxide) and poly(propylene oxide)]. When applied on human forearm skin, both GSNO-and SNAC-containing hydrogels increased blood flows over the 3 h study.…”
Section: Hydrogelsmentioning
confidence: 80%
“…The study suggested that F127 hydrogels might be used as the storage and controlled release material for S-nitrosothiols. A similar study was done by Seabra et al, [72] in which GSNO and SNAC were incorporated into Synperonic F-127 hydrogels [a triblock copolymer of poly(ethylene oxide) and poly(propylene oxide)]. When applied on human forearm skin, both GSNO-and SNAC-containing hydrogels increased blood flows over the 3 h study.…”
Section: Hydrogelsmentioning
confidence: 80%
“…The endogenous found molecule nitric oxide (NO) is not only a physiological mediator of important process such as the dilation of blood vessels [8,9], but also plays a key role in the immunological system against several pathogens [10][11][12]. Upon pathogen infection, activated macrophages and other immune cells inhibit pathogen replication by releasing several effector molecules, including NO [13].…”
Section: Introductionmentioning
confidence: 99%
“…7 The incorporation of NO donors into non-toxic polymeric matrices may allow the use of solid materials or gels for topical transdermal applications or subcutaneous implants. 8,9 Several peptides and proteins containing the sulfhidryl (SH) moiety in cysteine (Cys) residues, like glutathione (GSH), which are found endogenously in the tissues and plasma of mammals, are believed to be involved in the metabolism of NO.…”
Section: Introductionmentioning
confidence: 99%